MEMBINA KARAKTER SISWA YANG BERPERILAKU MENYIMPANG DI SDN 1 TILAHAN KECAMATAN HANTAKAN KABUPATEN HULU SUNGAI TENGAH - Miftahul Jannah (JURNAL SOCIUS, 2015)
This study aimed to describe the character of the student misbehaves and build student character misbehaves. This study used qualitative research methods. The results showed that students who misbehaves is caused by several factors, namely: family environmental factors and factors playmates were a bad influence. As for the coaching is done by the school is done by way of value investment approach or attitude finer such as faith, piety, honest, disciplined, responsible, mutual cooperation, fair, caring, resilient, obedience and respect.Keywords: build character, deviant behavior